Cardiovascular health profiles, systemic inflammation, and physical function in older adults: A population-based study. (June 2023) - Fan, Dong; Chen, Xia; Fa, Wenxin; Liang, Xiaoyan; Han, Xiaolei; Wang, Yongxiang; Cong, Lin; Liang, Yajun; Welmer, Anna-Karin; Hou, Tingting; Du, Yifeng; Qiu, Chengxuan
Highlights: A favorable CVH profile was associated with better physical function among rural chinese older adults. The association was partially mediated via low chronic systemic inflammation. This has implications for understanding the mechanisms linking CVH profile with physical function. Abstract: We examined the association of modifiable cardiovascular health (CVH) metrics with physical function among rural older adults in China and the potential role of inflammatory mechanisms in the association. This study included 3733 stroke- and dementia-free participants (age ≥65 years; 56.9% women) in the baseline survey of a multimodal intervention study in rural China. From March-September 2018, data were collected via face-to-face interviews, clinical assessments, and laboratory tests. The Short Performance Physical Battery (SPPB) test was performed to assess physical function. We defined six modifiable CVH metrics according to the modified American Heart Association's recommendations. Serum interleukin (IL)-6 was measured in a subsample ( n  = 1156). Data were analyzed with multiple general linear and logistic regression models and structural equation modeling. Poor physical function (SPPB score ≤9) was defined in 1443 participants. Ideal CVH (vs. poor CVH) was associated with multivariable-adjusted odds ratio of 0.60 (95%CI 0.48–0.75) for poor physical function. Ideal CVH was significantly associated with higher scores on balance, chair stand, and walking speed tests (all p  < 0.05). Moreover, ideal CVH profile was associated with lower serum IL-6 (multivariable-adjusted β=-0.04; 95% CI -0.06, -0.01). Mediation analysis revealed that serum IL-6 accounted for 14% of the association of CVH with total SPPB score and 10% of the association with walking speed score ( p  < 0.05). This study suggests that an ideal CVH profile is associated with better physical function among stroke- and dementia-free older adults, partly via inflammatory mechanisms. The preventive implications of these findings warrant further investigation in cohort studies.